OPTIMASI SINTESIS ASAM AZELAT DARI ASAM OLEAT DAN HIDROGEN PEROKSIDA MENGGUNAKAN KATALIS ASAM TUNGSTAT - Zuhrina Masyithah; Maria Paula Sihombing; Lawrena Valentine Br. Tohang (Talenta Publisher (Universitas Sumatera Utara), 2017)
Azealic acid is an oleochemical product which is an output from oleic acid with oxidation cleavage process and commonly its aplication in polymer industry such as nylon production, plastic industry, glue industry and also as fiber in polyester industry. The purpose of this research is to obtain comparison design and analysis of variance in two method of synthesis azelaic acid namely one step and two steps oxidation. The result design reviewed by Response Surface Methodology using Minitab 17 trial version program with percent mass of the catalyst variable, molar ratio of the substrate variable and temperature variable. Based on the statistic analysis the percentage conversion (Y)in one step Y : 97,99 + 3,907X1 + 3,651X2 – 4,556X3 – 1,467X12 – 4,299X22 – 4,453X32 + 0,57X1X2 + 0,63X1X3 + 1,37X2X3 and for two steps Y : 98,505 + 6,164X2 + 2,164X3-7,83X22-5,18X32. The design has R2 = 92,80 % for one step and 89,95 % in two steps.